RELASI KUASA DAN KEHENINGAN INSTITUSIONAL: ANALISIS FRAMING PEMBERITAAN CNN INDONESIA DAN KOMPAS.COM TENTANG KEKERASAN SEKSUAL DI PONDOK PESANTREN NDHOLO KUSUMO, PATI, DALAM PERSPEKTIF TEORI KRITIS ANTONIO GRAMSCI - Muhammad Nur Faza; Farhan Refas Alfiansyah; Rifma Ghulam Dzaljad (PT. Saha Kreasi Indonesia, 2026)
This article analyzes sexual violence at Pondok Pesantren Ndholo Kusumo, Pati, Central Java, through a framing analysis of two national news reports: CNN Indonesia (9 May 2026) and Kompas.com (29 June 2026), representing the moments of case disclosure and subsequent community backlash against the pesantren's closure. Using Entman's framing model and Critical Discourse Analysis (CDA), both reports are critiqued through Michel Foucault's power/knowledge theory and Antonio Gramsci's concept of hegemony. Findings show kiai authority operates productively in the Foucauldian sense through discipline and normalization, while CNN Indonesia's episodic-personal framing and Kompas.com's counter-narrative centered on parents both reproduce hegemony that protects the status quo. This article argues that institutional silence is neither natural nor resolved once disclosed, but a systemic power mechanism that continually mutates, dismantled only through structural and epistemic reform, including in how media frame such structural violence.